Enticing a Married Spouse: Legal and Moral Considerations Following the Abolition of Section 498 of the Penal Code - Saifuddin, Suhaizad; Beneldus, Bernard Noel (Kanun: Jurnal Undang-undang Malaysia; Vol 37 No 1 (2025): Kanun: Jurnal Undang-undang Malaysia Volume 37 Number 1 January 2025, 2025)
This article examines the abolition of the Offence of Enticing a Married Woman under Section 498 of the Penal Code and identifies laws related to morality and adultery from religious and historical perspectives. The study aims to propose recommendations for replacing the repealed provision with more appropriate legislation. A mixed-method approach was employed, involving both qualitative and quantitative methods. Data were collected through literature reviews, documentation, and surveys, and subsequently analysed using content analysis and descriptive methods, including frequency and percentage distributions. The findings indicate that the repeal of Section 498 aligns with the principles of gender equality as provided in the Federal Constitution. However, adultery remains as offense against cultural, moral, and religious values, particularly within the Muslim community in Malaysia. The repeal of this provision may have adverse implications for family and social institutions in the country. Consequently, this article advocates for the enactment of a new provision to address the offense of enticing a married spouse, regardless of whether the spouse is a husband or wife. Such provision is essential to uphold gender equality, in line with the principles upheld in the Federal Constitution. Keywords : Crime, enticing married women, morals, adultery, family, society Full Text :  PDF